PENGARUH BIAYA LINGKUNGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN DENGAN KINERJA LINGKUNGAN SEBAGAI PEMEDIASI ( Studi Empiris Pada Perusahaan Terdaftar di BEI yang Mengikuti PROPER Tahun 2016-2018) - Meri, Handayani; Ria, Sari Nelly; Eka, Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to analyse the effect of environmental cost and corporate social responsibility (CSR) disclosure on financial performance with environmental performance as a mediated (empirical study on companies listed on Indonesia Stock Exchange which following PROPER year 2016-2018)